Motivasi Intrinsik Pegawai Pada Kantor Camat Sarolangun Kabupaten Sarolangun - Firmasari, Puja; Setiani, Revia (Jurnal Dinamika Manajemen, 2024)
The data collection procedure involved distributing a questionnaire that was structured with a list of questions relating to intrinsic motivation. The results of the questionnaires showed that the mean score for innovation was 145, while that for feedback was 155, risk 149, responsibility 155, friendship 149, cooperation 143, conflict 150, trust 149, contribution 145, and duty 149. The research findings show that employees in the Sarolangun sub-district office are highly motivated in terms of feedback, risk, friendship, and conflict. However, the aspects of innovation, cooperation, trust, and assigned tasks require more attention and improvement from the Sarolangun sub-district office agency in Sarolangun Regency